2013
DOI: 10.1371/journal.pone.0056072
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Aminotransferase Is Associated with an Adverse Nocturnal Blood Glucose Profile in Individuals with Normal Glucose Regulation

Abstract: ObjectiveAlthough the association between alanine aminotransferase (ALT) levels and risk of type 2 diabetes is well-studied, the effects of slightly increased ALT levels within the normal range on the temporal normal glucose profile remains poorly understood.MethodsA total of 322 Chinese subjects without impaired glucose tolerance or previous diagnoses of diabetes were recruited for study from 10 hospitals in urban areas across China. All subjects wore a continuous glucose monitoring (CGM) system for three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Increased circulating levels of alanine and glutamine on HFD most likely originate from muscle proteolysis and metabolism of BCAA, with increased release of BCKA. Our atlas suggests further investigation of serum alanine as a biomarker for T2DM and cardiovascular disease risk is warranted, in keeping with findings on alanine aminotransferase (ALT) (Vozarova et al, 2002; Zhou et al, 2013) and recent indications in human T2DM patients (Isherwood et al, 2017). We thus propose a more general “risk network” of alanine-related metabolites and enzymatic biomarkers.…”
Section: Discussionsupporting
confidence: 79%
“…Increased circulating levels of alanine and glutamine on HFD most likely originate from muscle proteolysis and metabolism of BCAA, with increased release of BCKA. Our atlas suggests further investigation of serum alanine as a biomarker for T2DM and cardiovascular disease risk is warranted, in keeping with findings on alanine aminotransferase (ALT) (Vozarova et al, 2002; Zhou et al, 2013) and recent indications in human T2DM patients (Isherwood et al, 2017). We thus propose a more general “risk network” of alanine-related metabolites and enzymatic biomarkers.…”
Section: Discussionsupporting
confidence: 79%
“…However, our results may indicate that daily 3-meal pattern with different dietary protein contents may affect amino acid requirements and metabolic availability. It has been reported recently that elevated ALT levels, within the normal physiological range, are associated with unfavorable nocturnal glucose profiles in Chinese subjects with normal glucose regulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Faba bean diet showed higher ALT levels, but the results fall in the physiological range for this parameter. Zhou et al (2013) observed similar cases in human patients with normal glucose regulation and hypothesised that it was due to an unfavourable nocturnal glucose profile and they suggested that liver enzymes may be a marker of an adverse glucose profile.…”
Section: Discussionmentioning
confidence: 83%